Medical prescription of physical exercises in hypertension blood pressure - J.C. Cruz; B. Cueto; A. Fernández; L. García (Asociación Española de Ciencias del Deporte, 2010)
Physical exercise forms part of the treatment of high blood pressure, based on aerobic activity. However, training and control parameters have not been clearly defined. The purpose of the present study was to establish the control parameters for blood pressure during training for use in normalizing blood pressure. Among the most important factors are standard methods for recording blood pressure, identification of associated risk factors, ensuring that the subject exercises regularly, at least three times per week, attainment of an VO2 max. of close to 60%, and medical treatment compatible with physical exercise. KEY WORDS: Blood Pressure, Hypertension and Physical Exercise.